Fibromyalgia syndrome—am I an autoimmune condition? - Andreas Goebel (PAIN Reports)
Abstract. Assessments of serum-autoantibodies in fibromyalgia syndrome (FMS) date back to the 1980s and have yielded inconsistent results. Based on a new passive transfer paradigm, since 2021 causative involvement of immunoglobulin G–mediated autoimmunity in severe FMS has been demonstrated in several studies, which have included UK, Swedish, and Canadian patients. These findings open the path to the development of novel diagnostic and immune-therapeutic approaches. Autoantibody targets and downstream mechanisms and the molecular processes that translate infection-, toxicity-, or stress-triggers into the FMS immune response in genetically or otherwise vulnerable individuals require study. These results in FMS also suggest that other chronic pain conditions or nonpainful symptom-based disorders may similarly be caused by noninflammatory minimally destructive autoantibody-mediated autoimmunity, thus offering hope for large groups of patients.